2020
DOI: 10.1007/s00401-020-02243-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary mismatch repair deficient IDH-mutant astrocytoma (PMMRDIA) is a distinct type with a poor prognosis

Abstract: Diffuse IDH-mutant astrocytoma mostly occurs in adults and carries a favorable prognosis compared to IDH-wildtype malignant gliomas. Acquired mismatch repair deficiency is known to occur in recurrent IDH-mutant gliomas as resistance mechanism towards alkylating chemotherapy. In this multi-institutional study, we report a novel epigenetic group of 32 IDH-mutant gliomas with proven or suspected hereditary mismatch repair deficiency. None of the tumors exhibited a combined 1p/19q deletion. These primary mismatch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…PMMRDIA were histologically high-grade and were mainly found in younger patients (median age 14 years) and all of them had a defective MMR system. They also reported that compared to reference cohorts of other IDH-mutant gliomas, PMMRDIA had by far the worst clinical outcome with a median survival of only 15 months irrespective of histological or molecular features [ 163 ].…”
Section: Mismatch Repairmentioning
confidence: 99%
“…PMMRDIA were histologically high-grade and were mainly found in younger patients (median age 14 years) and all of them had a defective MMR system. They also reported that compared to reference cohorts of other IDH-mutant gliomas, PMMRDIA had by far the worst clinical outcome with a median survival of only 15 months irrespective of histological or molecular features [ 163 ].…”
Section: Mismatch Repairmentioning
confidence: 99%
“…DNA extraction was performed as previously described [35]. DNA methylation profiles were generated using the Infinium HumanMethylation450 (450 k) or Infinium MethylationEPIC (850 k) BeadChip array (Illumina, San Diego, USA) according to the manufacturer's instructions.…”
Section: Dna Methylation and T-sne Analysismentioning
confidence: 99%
“…Reference cases were selected based on a high classifier score (> 0.9) in the brain tumor classifier. Methylation of the O 6 -alkylguanine DNA alkyltransferase (MGMT) promoter region was calculated as described previously [35].…”
Section: Dna Methylation and T-sne Analysismentioning
confidence: 99%
“… 34 This genetic distinction was confirmed with DNA methylation profiling and has recently been refined to identify a clinically-distinct subtype (e.g. mismatch repair-deficient 35 ). For many of the newly-described tumor types, however, methylation profiling has largely served as a tool for discovery.…”
Section: Novel and Rare Tumor Typesmentioning
confidence: 84%